2022
DOI: 10.1093/brain/awab475
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of amygdala circuits during sepsis prevents the development of anxiety-related behaviours

Abstract: Sepsis is a life-threatening condition induced by a deregulated host response to severe infection. Post-sepsis syndrome includes long-term psychiatric disorders, such as persistent anxiety and post-traumatic stress disorder, whose neurobiological mechanisms remain unknown. Using a reference mouse model of sepsis, we showed that mice that recovered from sepsis further developed anxiety-related behaviours associated with an exaggerated fear memory. In the brain, sepsis induced an acute pathologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 95 publications
1
10
0
Order By: Relevance
“…There is also evidence showing that changes within CeA circuit are implicated in inflammatory-related mental disease. For example, a recent study showed that in a mouse model of sepsis induced by intraperitoneal infection, the mice exhibited anxiety-like behavior and exaggerated fear memories, which are similar to anxiety and PTSD-like symptoms seen in human sepsis survivors [ 155 ]. It was found that sepsis induces the acute pathological activation of CeA-specific neuron types that project to the ventral BNST and transient and targeted silencing of this subpopulation using chemogenetic methods during the acute phase of sepsis can prevent the subsequent development of anxiety-related behaviors [ 155 ].…”
Section: Amygdala Neuroinflammation and Psychiatric Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also evidence showing that changes within CeA circuit are implicated in inflammatory-related mental disease. For example, a recent study showed that in a mouse model of sepsis induced by intraperitoneal infection, the mice exhibited anxiety-like behavior and exaggerated fear memories, which are similar to anxiety and PTSD-like symptoms seen in human sepsis survivors [ 155 ]. It was found that sepsis induces the acute pathological activation of CeA-specific neuron types that project to the ventral BNST and transient and targeted silencing of this subpopulation using chemogenetic methods during the acute phase of sepsis can prevent the subsequent development of anxiety-related behaviors [ 155 ].…”
Section: Amygdala Neuroinflammation and Psychiatric Disordersmentioning
confidence: 99%
“…For example, a recent study showed that in a mouse model of sepsis induced by intraperitoneal infection, the mice exhibited anxiety-like behavior and exaggerated fear memories, which are similar to anxiety and PTSD-like symptoms seen in human sepsis survivors [ 155 ]. It was found that sepsis induces the acute pathological activation of CeA-specific neuron types that project to the ventral BNST and transient and targeted silencing of this subpopulation using chemogenetic methods during the acute phase of sepsis can prevent the subsequent development of anxiety-related behaviors [ 155 ]. Considering inflammatory chronic pain increases the risk of depression, Zhou and colleagues identified a novel pathway involving 5-HT projections from the dorsal raphe nucleus to somatostatin-expressing interneurons in the CeA, and then to the lateral habenula for comorbid depressive symptoms in chronic pain [ 156 ].…”
Section: Amygdala Neuroinflammation and Psychiatric Disordersmentioning
confidence: 99%
“…Optogenetic stimulation of CeA→basolateral amygdala circuits can induce these behaviors (Tye et al, 2011), but based on our tracing studies, these are distinct from AVPR1A CeA neurons. Chemogenetic inhibition of CeA→BNST circuits prevents anxiety-related behavioral adaptations in the context of sepsis (Bourhy et al, 2022). Since they did not target their manipulations to a genetically defined subpopulation of neurons, it is possible that some AVPR1A CeA neurons contributed to this effect.…”
Section: Discussionmentioning
confidence: 99%
“…Gut-innervating nociceptors can be activated by Salmonella enterica and release a neuropeptide that modulates both the density of Peyer patches’ M cells and the levels of segmentous filamented bacteria, leading to a protection against infection ( 51 ). A specific neuronal population of the central nucleus of the amygdala was found to be activated in the brain of mice recovering from experimental sepsis, leading to anxiety-related behavior and exaggerated fear memory similar to the long-term anxiety and post-traumatic stress disorder-like syndrome observed following sepsis in humans ( 52 ).…”
Section: Crosstalk Between the Two Systems Of Relationmentioning
confidence: 92%